“Online Learning” untuk Meningkatkan Kemampuan Bahasa Inggris Siswa di Masa Pandemi Covid-19 - Novita Al Ihyak Dieni; Kristin Marwinda (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This community service activity is included to the community partnership program. The targets are people who are not economically productive, they are the students of elementary school (SD), junior high school (SMP), and senior high school (SMA) in Pondok Babadan Baru, RT.01, RW. 13, Beji, East Ungaran. The activities carried out in this program are handling problems in learning English for students during the COVID-19 pandemic. According to most students, English subject is a difficult subject. To make it being easy, it needs a practice when we learn a language. In fact, most students do not use English in their daily life. One of the reasons is because of unsupportive environment, such as parents who cannot speak English. Another problem is in the learning system used in the pandemic era that is online learning. Even though students are familiar with technology, the technology used for learning is still foreign to them. Therefore, this community service activity will help students increasing their motivation in learning English during the pandemic so that their ability in reading, listening, speaking and writing using English can improve. The method of service activities applied is in the form of assistance in learning English through Google Meet application. The result of this service activity is increased students’ motivation in learning English during the pandemic which makes students to be confident in using English. The results of this activity are expected to be used as guidelines in dealing with children's problems in learning during the COVID-19 pandemic.